2022
DOI: 10.1186/s12935-022-02793-7
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal circular RNA: a signature for lung cancer progression

Abstract: Membrane vesicles having a diameter of 30–150 nm are known as exosomes. Several cancer types secrete exosomes, which may contain proteins, circular RNAs (circRNAs), microRNAs, or DNA. CircRNAs are endogenous RNAs that do not code for proteins and can create continuous and covalently closed loops. In cancer pathogenesis, especially metastasis, exosomal circRNAs (exo-circRNAs) have a crucial role mainly due to the frequently aberrant expression levels within tumors. However, neither the activities nor the regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 209 publications
0
11
0
Order By: Relevance
“…Although the functions and molecular mechanisms of circRNAs in cancer remain largely unknown, the role of miRNA sponge of circRNAs and the circRNA‐miRNA‐mRNA axis were one of the most important parts 18,19 . circRNAs have also been found in exosomes and could be transferred between different cells via exosomes to realize their functions 20–22 . The significant roles of exosomal circRNAs have also been explored in various cancers, including breast cancer 23–25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the functions and molecular mechanisms of circRNAs in cancer remain largely unknown, the role of miRNA sponge of circRNAs and the circRNA‐miRNA‐mRNA axis were one of the most important parts 18,19 . circRNAs have also been found in exosomes and could be transferred between different cells via exosomes to realize their functions 20–22 . The significant roles of exosomal circRNAs have also been explored in various cancers, including breast cancer 23–25 .…”
Section: Discussionmentioning
confidence: 99%
“…18,19 cir-cRNAs have also been found in exosomes and could be transferred between different cells via exosomes to realize their functions. [20][21][22] The significant roles of exosomal circRNAs have also been explored in various cancers, including breast cancer. [23][24][25] However, most research has focused on the functions of one exosomal circRNA and has ignored the complex ceRNA networks.…”
Section: Discussionmentioning
confidence: 99%
“…Circular RNAs (CircRNAs) are an emerging field in cancer research, especially in NSCLC, as they were demonstrated to play pivotal roles in carcinogenesis, tumour formation, proliferation, migration, invasion, and sensitivity to therapy [76] . The first evidence of the presence of circRNA in cancer EVs was reported in 2015 when Li et al, using RNA-seq methods, demonstrated the enrichment of circRNAs in tEVs compared to the cell of origin [77] . However, although many efforts have been made in recent years to understand the role of circRNAs in cancer progression, their impact on NSCLC has not been investigated as carefully as that of other types of non-coding RNAs.…”
Section: Circular Rnasmentioning
confidence: 99%
“…CircRNAs are a class of circular endogenous non-coding RNAs without a 5’ segment cap and 3’ end poly(A) tail structure, formed by covalent bonding, which are mRNA precursors (pre-mRNAs) produced by reverse splicing (back-splicing) and are widely expressed in eukaryotic cells as circular endogenous molecules. The abundance of circRNAs in exosomes is twice as high as in cells, and studies have shown that circRNAs are involved in key processes in the development of lung cancer ( 15 ).…”
Section: Introductionmentioning
confidence: 99%